„Nad Pismo Święte przyczyniać”. Kontekst teologiczny sceny zstąpienia do piekieł w Historyi o chwalebym Zmartwychwstaniu Pańskim Mikołaja z Wilkowiecka - Paweł Bondaruk (Meluzyna: dawna literatura i kultura, 2014)
The article reflects upon the scene of the Descent into Hell from Historyja o chwalebnym ZmartwychwstaniuPańskim, in the theological context. The reading of the Easter mystery play fromthe perspective of the Church fathers and Medieval writers is explained by the author himself,Mikołaj from Wilkowiecko (16th century). The conflict between God and Satan, the climax ofthe mystery play, is presented from three angles: as a dialogue of the omniscience and ignorance,a battle of the omnipotence and impotence and a dispute between law and chaos.